Change-Oriented Organizational Citizenship Behavior pada karyawan: Bagaimana peranan kepemimpinan transformasional? - Pramesta, Robbana Rizka Amelia; Sofiah, Diah; Prasetyo, Yanto (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2024)
Abstract Change-Oriented Organizational Citizenship Behavior (OCB) is a constructive effort by individuals to identify and implement changes that companies need because behavior is not enough to help, but employee behavior is important in improving working methods, policies, and procedures to improve situations and performance. Transformational leadership can influence the emergence of Change-Oriented OCB behavior as an external factor because the motivation and invitation to bring about change in the organization make employees active participants in the development of the company. The aim of this study is to find out the relationship between transformational leadership and Change-Oriented OCB. This study is a quantitative correlational study involving a total population of 90 respondents. The scale of measurement of transformational leadership variables and Change-Oriented OCBs using the Likert scale. The results of the test were tested using product moment analysis. The correlation test results between transformational leadership and Change-Oriented OCBs produced a very significant positive relationship, which means that it can be concluded that the higher the transformational leader, the higher is the Change-Oriented OCB, on the contrary that the lower the transformational leadership, the lower is the changing-oriented OCB. Keywords: Change-Oriented OCB; Employee; Transformational Leadership Abstrak Change-Oriented Organizational Citizenship Behavior (OCB) adalah usaha konstruktif yang dilakukan individu untuk mengidentifikasi dan menerapkan perubahan yang dibutuhkan perusahaan karena perilaku membantu saja tidak cukup melainkan perilaku karyawan penting dalam meningkatkan metode kerja, kebijakan, dan prosedur untuk memperbaiki situasi dan kinerja. Kepemimpinan transformasional dapat mempengaruhi munculnya perilaku Change-Oriented OCB sebagai faktor eksternal karena motivasi dan ajakan untuk memberikan perubahan pada organisasi membuat karyawan menjadi turut serta aktif pada perkembangan perusahaan. Tujuan dari penelitian ini adalah untuk mengetahui hubungan antara kepemimpinan transformasional dengan Change-Oriented OCB. Penelitian ini merupakan penelitian kuantitatif korelasional yang melibatkan keseluruhan populasi sejumlah 90 responden. Skala pengukuran pada variabel kepemimpinan transformasional dan Change-Oriented OCB menggunakan skala likert. Hasil penelitian diuji menggunakan uji analisis product moment. Hasil uji korelasi antara antara kepemimpinan transformasional dengan Change-Oriented OCB menghasilkan hubungan positif yang sangat signifikan, artinya dapat disimpulkan bahwa semakin tinggi kepemimpinan transformasional, maka semakin tinggi pula Change-Oriented OCB, sebaliknya bahwa semakin rendah kepemimpinan transformasional, maka semakin rendah pula Change-Oriented OCB. Kata kunci: Change-Oriented OCB; Karyawan; Kepemimpinan Transformasional